2011
DOI: 10.1111/j.1365-2672.2011.05190.x
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic activity and mode of action of flavonoids isolated from smaller galangal and amoxicillin combinations against amoxicillin-resistant Escherichia coli

Abstract: Aim:  The smaller galangal is extracted, purified and identified the bioactive compounds. The purpose of this research was to investigate whether these isolated compounds have antibacterial and synergistic activity against amoxicillin‐resistant Escherichia coli (AREC) when used singly and in combination with amoxicillin. The primarily mode of action is also studied. Method and Results:  The galangin, kaempferide and kaempferide‐3‐O‐β‐d‐glucoside were isolated. The minimum inhibitory concentrations(MIC) of amox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
46
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(54 citation statements)
references
References 35 publications
(34 reference statements)
8
46
0
Order By: Relevance
“…Kaempferide has been shown to lower the MIC of amoxicillin against amoxicillin resistant E. coli (AREC) when used in combination with this antibiotic [33]. These earlier findings together with our current results provide a strong support of the quorum quenching activity of kaempferide and its application in antimicrobial combination strategies.…”
Section: Screening For Qs Inhibition Using a Flavonoid Collectionsupporting
confidence: 72%
“…Kaempferide has been shown to lower the MIC of amoxicillin against amoxicillin resistant E. coli (AREC) when used in combination with this antibiotic [33]. These earlier findings together with our current results provide a strong support of the quorum quenching activity of kaempferide and its application in antimicrobial combination strategies.…”
Section: Screening For Qs Inhibition Using a Flavonoid Collectionsupporting
confidence: 72%
“…According to Osawa et al (1995), the enhanced growth responses indicate increased nutrient digestion and antioxidant effects of curcumin. Our results are in agreement with those of few other studies that revealed the stimulatory effects of turmeric on lipase activity, digestive enzyme activity and acid and alkaline protease activity, which all enhance the yellow pigmentation and growth rate of fish (Eumkeb et al, 2012;Kang et al, 2011). Crude protein is known to be significantly augmented while ether content decreases in fish response to turmeric supplementation (Cao et al, 2015).…”
Section: Discussionsupporting
confidence: 83%
“…The antibacterial activity of flavonoids can be exerted in three ways: directly kill the bacteria, synergistically activate the antibiotics, and attenuate the bacterial pathogenicity [16]. It is worth mentioning that the flavonoids have shown inhibitory activity against the efflux pump of MRSA [17], and also restrained the synthesis of peptidoglycan and ribosome in the cells of amoxicillin-resistant Escherichia coli (AREC) [18]. They have also shown inhibitory activity against different kinds of -lactamases produced by bacteria which are the key enzymes that disable the common antibiotics [19][20][21].…”
Section: Introductionmentioning
confidence: 99%